A high impact intervention for a high impact intervention: Improving documentation of peripheral venous access insertion in theatre. Issue 1 (January 2018) - Upadhyaya, Kavita; Hendra, Heidy; Wilson, Nick
The Department of Health's 'High Impact Intervention (HII) – Peripheral intravenous cannula care bundle' lists six actions to be performed at the time of peripheral intravenous cannulation. Audit of compliance to these requires documentation. We assessed documentation on the anaesthetic charts of 50 surgical patients. Purpose-made stickers were then placed on all anaesthetic charts. Re-assessment of a further 50 patients' charts demonstrated a significant improvement in documentation of the bundle post intervention (Fisher's exact test P < 0.0001). This is an example of how a low-tech intervention can produce a high impact improvement in documentation.